CHOOSING THE PHENOMENOLOGICAL APPROACH TO EXPLORE A LIVED EXPERIENCE: METODOLOGICAL COMPARISON - Zuitiņš, Juris; Pipere, Anita; Sudraba, Velga (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
With the escalating use of qualitative methods in health psychology, the need for the careful match between the studied topic and research design has been repeatedly stressed. The purpose of this study is to choose and substantiate the most compatible methodological approach for the use in the prospective phenomenological doctoral research investigating a lived experience of fathers of fatally ill child. This methodological paper compares three main phenomenological research approaches: Hermeneutic Phenomenology (van Manen, 1990), Psychological or Transcendental Phenomenology (Moustakas, 1994) and Interpretative Phenomenological Analysis (Smith, 1996). The comparative analysis of these three approaches to phenomenological research shows that the Interpretative Phenomenological Analysis could be viewed as the most appropriate approach for analyzing the lived experience of fathers of fatally ill child considering the specific sample of this study, character of the research topic and experience of researcher with phenomenological studies. The methodological underpinnings and possible issues of chosen approach have been discussed at the end of paper.